Der Steinkohlenbergbau im oberschlesischen Becken während des zweiten Weltkrieges [Coal mining in the Upper Silesian Basin during the Second World War] - Jaros, Jerzy (Studia Historiae Oeconomicae, 1979)
This article analyzes the development and condition of coal mining in the Upper Silesian Basin during the German occupation in World War II. Before the war, the region was one of the most important coal-producing areas in Europe, encompassing both Polish and German territories. The political reorganization after 1939 led to the integration of Polish mines into the German economic system, with far-reaching consequences for ownership structures, production methods, and technical infrastructure. The aim of the study is to document and evaluate the changes in the mining sector during the war years, particularly with regard to production, organization, labor force, and long-term effects. The author draws on official statistics, reports of the Polish Central Coal Administration (CZPW), archival materials, and scholarly literature on German occupation and economic policy. The study shows that between 1939 and 1944, approximately 420 million tons of coal were extracted in the Upper Silesian Basin—an amount equivalent to the reserves of several large mines. The use of forced labor and prisoners of war, along with the neglect of investments, led to severe wear of machinery and equipment. Technical innovations were hardly introduced, and many development projects remained unrealized. Excessive exploitation resulted in a continuous decline in coal output per worker. After the war, a production decrease of up to 18% compared to 1938 was recorded. The total damages in the Polish coal industry were estimated at around 3.2 billion złoty, while the investments made during the occupation covered only about 3.6% of that value. Full restoration of production capacity was not achieved until 1948.